2009
DOI: 10.1002/hed.21185
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo gene therapy using autologous dermal fibroblasts expressing hLMP3 for rat mandibular bone regeneration

Abstract: These results suggest that the experimental approach based on transplantation of genetically modified autologous cells could provide an alternative treatment for cranio-maxillo-facial defects. Nonetheless, additional data from the study on larger bone defects must follow to foresee a clinical application in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…4 The distribution and viability of living cells adsorbed on the HA/COL composite have been demonstrated in a previous study 15 : enhanced green fluorescence proteinexpressing fibroblasts adsorbed on the same scaffold were homogeneously seeded and expressed the transgene 1 month after implantation in the rat mandible.…”
Section: Cell Preparationmentioning
confidence: 90%
See 1 more Smart Citation
“…4 The distribution and viability of living cells adsorbed on the HA/COL composite have been demonstrated in a previous study 15 : enhanced green fluorescence proteinexpressing fibroblasts adsorbed on the same scaffold were homogeneously seeded and expressed the transgene 1 month after implantation in the rat mandible.…”
Section: Cell Preparationmentioning
confidence: 90%
“…In particular, the use of either plasmid or viral vectors is burdened with toxic effects and immunologic issues that must be considered before translating such experimental procedures to the bedside. 4,14 The present study showed that human ATSCs, which were neither differentiated nor engineered before transplantation, implanted on a collagen-hydroxyapatite-based scaffold induced partial bone healing in an experimental model of rat mandibular defect. Although the bone defect was not completely healed, the bone regeneration allowed the functional recovery of treated rats.…”
Section: Commentmentioning
confidence: 95%
“…However, despite significant evidence of their potential benefit to bone repair there is, to date, a dearth of convincing clinical trials (Gautschi et al, 2007). On this regard, the main limitation of using recombinant proteins for inducing bone formation in clinical applications is the need for delivery systems that provide a sustained, biologically appropriate concentration of the osteogenic factor at the site of the defect (Lattanzi et al, 2008;Parrilla et al, 2010).…”
Section: Bone Morphogenetic Proteins (Bmps)mentioning
confidence: 99%
“…Liu et al, 2002;Viggeswarapu et al, 2001). Despite the truncation of nearly two third of the full-length isoform, LMP3 retains efficient osteogenic properties, demonstrated in vitro and in different animal models (Lattanzi et al, 2008;Parrilla et al, 2010;Pola et al, 2004). In vitro, both LMP1 and LMP3 induce osteogenic differentiation of mesenchymal progenitors, fibroblasts and pre-osteoblasts, through the transcriptional activation of BMP-family members (mainly BMP2, BMP4 and BMP7) and TGFβ1 protein (Bernardini et al, 2010 ;Minamide et al, 2003).…”
Section: Lim-mineralization Proteinsmentioning
confidence: 99%
See 1 more Smart Citation